Internal Bleaching As An Esthetic Management For Discolored Non-Vital Tooth Post-Endodontic Treatment: Case Report - Alvinny Ganeshaputri; Opik Taofik Hidayat; Dudi Aripin (Maranatha Christian University, 2026)
Abstract Background: Dental trauma may lead to pulpal necrosis, resulting in internal degradation of dental tissues and subsequent discoloration of the affected tooth. This discoloration is commonly associated with degradation of pulp remnants, penetration of obturation materials into dentinal tubules, or hemolysis of erythrocytes during endodontic procedures. Internal bleaching offers a minimally invasive and biologically conservative approach for esthetic rehabilitation in these cases. Objective: To present a clinical case demonstrating the application of internal bleaching using the walking bleach technique for the esthetic management of a non-vital, endodontically treated maxillary central incisor. Case Report: A 25-year-old female visited RSGM Unpad with a discolored maxillary left central incisor (#21) and worsen her appearance. The patient’s previous history of trauma five years ago. Clinical and radiographic examinations confirmed pulp necrosis, with asymptomatic apical periodontitis. Root canal treatment was performed using standar protocol. Two weeks post obturation, internal bleaching was initiated using the walking bleach technique with 35% hydrogen peroxide. The coronal seal was ensured using a 2 mm cervical barrier of resin-modified glass ionomer cement to prevent cervical resorption. After two bleaching sessions, a satisfactory shade match with adjacent teeth was achieved without any complications. Conclusion: Internal bleaching with the walking bleach technique provides an effective, conservative, and predictable solution for managing discolored in non-vital teeth. The use of a proper cervical barrier and careful case selection are essential to minimize risks. This approach provides favorable esthetic results while preserving tooth structure. Keyword: Internal bleaching, esthetics, non-vital tooth, tooth discoloration, endodontic